Influencing weight bias: The impact of biased questionnaire anchors on stereotype beliefs and judgments. Issue 5 (September 2015) - Carels, R.A.; Rossi, J.; Taylor, M.; Borushok, J.; Kiefner-Burmeister, A.; Cross, N.; Hinman, N.; Burmeister, J.M.
Summary: Objectives: In this investigation, biased questionnaire response anchors were designed to indirectly manipulate respondents' estimates of their peers' stereotypic beliefs or the estimates of scientific research findings about individuals with obesity. The current study tested the hypothesis that biased response anchors could influence personal beliefs about obesity. Methods: Two-hundred adults participated in the study. A simple manipulation of questionnaire items (i.e., asking respondents to estimate peers' beliefs or scientific research findings) using biased response scale anchors was designed to subtly relay information about certain personality traits of individuals with obesity. Results: The anchor manipulation significantly influenced participants' immediate and follow-up weight biased beliefs as well as participants' evaluation of an obese job applicant's potential for employment. Conclusion: Social judgments about obese individuals may be susceptible to subtle manipulation of response anchors and may be impacted by the source of comparison information (e.g., peers; scientific research).